The Effect of Vitamin C Cream on Pregnancy Striae in Primiparous Women: A Randomized Controlled Clinical Trial - Hadis Taheri; Masoomeh Kheirkhah; Ali Ghobadi; Nooshin Eshraghi; Shima Haghani (Iran University of Medical Sciences, 2024)
Background: Pregnancy striae, which are highly prevalent, cause significant cosmetic concerns for most women and pose challenges regarding its prevention and treatment. The present study was conducted to determine the effect of vitamin C cream on pregnancy striae in primiparous women. Methods: This study was a randomized controlled clinical trial conducted on 60 primiparous women with a gestational age of 18-20 weeks who were referred to Shahid Akbarabadi Hospital in Tehran City, Iran, from July 2022 to January 2023. The subjects were recruited by continuous sampling and then assigned to the intervention (n=30) and placebo (n=30) groups using blocked randomization with the Sealed Envelope online software. The intervention group used the creams twice a day for 4 months on the skin of the abdomen, thighs, breasts, and buttocks. The control group used the placebo cream in the same way as the intervention group. The severity and number of striae were assessed using the Atwal striae gravidarum (SG) score. The assessments were performed before the intervention and also in the 4th, 8th, 12th, and 16th weeks after the start of the intervention. The data were analyzed using descriptive statistics (relative frequency and Mean±SD) and inferential statistics (the chi-square test and independent t-test) using SPSS software, version 16. The significance level was set at P<0.05. Results: There were no significant differences between the two groups in terms of personal and midwifery characteristics (P>0.05). However, a significant difference was observed between the two groups regarding the incidence of pregnancy striae at all follow-up times. The use of vitamin C cream had a significant effect in reducing the number and severity of pregnancy striae (P<0.001). Conclusion: Considering the effectiveness of vitamin C in preventing pregnancy striae and its affordability, safety, and acceptability for pregnant women, it can be recommended for the prevention of pregnancy striae.